Socioeconomics and environmental perception of lobstermens professionals in Continental Shelf Amazon (Research, Society and Development, 2020)
The objective was to verify the socioeconomic profile of the lake professionals and their perception of the “lobster” fishing system on the north coast of Brazil. 40 professionals were interviewed, including shipowners, masters and fishermen residing in the cities of Augusto Corrêa and Bragança (Pará), using the “Bola de Neve” technique, between September/14 and December/15. A list of 41 attributes, in the form of categorical variables, was created to characterize the “lobster” fishing system. The interviewees were male, aged between 21 and 60 years. Of these, 62.5% were born in the state of Ceará and have a low level of education (60%). Interviewees' income ranged from R$ 800.00 to R$ 19,000.00/trip, reflecting the good basic conditions of housing and health, except for some fishermen. Work accidents were reported by masters (20%) and fishermen (15%) during fisheries. Based on the interviewees' perception, particular patterns for the “lobster” fishing system were listed. In general, the social, economic and environmental dimensions stood out, indicating the importance of this activity in family maintenance, as well as satisfactory environmental characteristics. In contrast, the technological and sustainability dimensions, since the processing and conservation of the lobster on board are inadequate, leading to low quality, compromising their commercialization.